Relación del microbioma de la leche materna humana con enfermedades autoinmunes y neurodegenerativas. - Castillo Belén, Juan Ramón; Pardo Gómez, María Elena; Hernández, Leonardo Ramos; Rodríguez Beltrán, Nancy María (MEDISAN, 2026)
Traditionally, human breast milk (HBM) was thought to be devoid of microorganisms. Today, it is known as a unique food for infants, containing a significant number of living organisms and countless bacteria, viruses, archaea, eukaryotes such as fungi, and even protozoa that have physiological, metabolic, and immunological functions. These organisms comprise the microbiota of human milk and exert a protective effect. The objective of this work is to describe important aspects of the microbiota of human breast milk and its interrelation with the development of major autoimmune and neurodegenerative diseases. This work employs theoretical methods such as systematization, analysis-synthesis, systemic-structural, and functional approaches in the pursuit of scientific knowledge. Through the study and review of scientific literature and its theoretical-methodological analysis, it is concluded that the microbiota of human breast milk has unique characteristics. Furthermore, it plays a role in the brain-gut-microbiota axis and establishes communication with the central nervous, enteric nervous, endocrine, and immune systems. The disruption of the balance of the intestine leads to the development of autoimmune and neurodegenerative diseases.